Spatial conditions for development of activation of peripheral areas: the case of northern Poland - Jacek Sołtys (European Regional Science Association (ERSA), 2012)
The areas located outside metropolitan areas and also outside areas activated through other big cities are called peripheries. There are big differences between the levels of development of metropolitan and peripheral areas in Poland. There are also great differences in opportunities to development including the location of new investment. Peripheral areas are characterized by features such as: high unemployment, relatively impoverished populations, low productivity, low territorial accessibility, small development potential. Lack of development factors is the cause of low development level. Peripheral areas are differential. The author analyses this differentiation, including location of development factors in peripheral areas of northern Poland. Touristic values are such factor, but tourism is mainly seasonal. The tourist season is short, 2-4 months. The development of this tourism increases the income of people and business, but the increase of permanent work-places is small. The lack of robust businesses that are able to start constant and stable development is one of the main weakness of peripheral areas. Bed transport accessibility is the other weakness of peripheral areas. As one of the factors of socio-economic development considered by author is the spatial structure, including settlement network. In some areas lack of appropriately big node could be the weakness of such network. The analysis of case study area is conducted on the basis of the features of poviats (counties), which are described by following indicators: employees in the industry sector and market service sector per 1000 population of working age, number of entities in national economy between 10-49 and more than 49 workers per 1000 population of working age, investment outlays in enterprises per capita in the years 2008-2010, gross value of fixed assets in enterprises per capita, average monthly gross wages and salaries, unemployment rate, participation of the urban population, population of the biggest settlement node. The author researches correlation between features presented above. In the next part of the paper the author performs a typology of poviats. In the last part of the paper regional policy of stimulating growth is proposed.
Keywords: 330